2014
DOI: 10.2478/orga-2014-0015
|View full text |Cite
|
Sign up to set email alerts
|

Managing Customer Participation and Customer Interactions in Service Delivery: the Case of Museums and Educational Services

Abstract: Background and Purpose -In this study we investigate determinants of customers' quality perceptions in service processes which involve customer participation and customer to customer interaction (CCI). Building on existing multidimensional approaches to service quality we explore relevant quality aspects for related to the performance customer participation and CCI. Design/Methodology/Approach -The study builds on focus groups conduct with employees and customers of a leading provider of educational and scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Shevlin (2007) suggested that the greater the customer's engagement frequency and repetitability, the more relationship attachment is generated. Amorim et al (2014) also indicated that customer engagement behaviour might increase customer satisfaction. Thus, we propose the following hypotheses.…”
Section:  Social Community Member Relationshipmentioning
confidence: 99%
“…Shevlin (2007) suggested that the greater the customer's engagement frequency and repetitability, the more relationship attachment is generated. Amorim et al (2014) also indicated that customer engagement behaviour might increase customer satisfaction. Thus, we propose the following hypotheses.…”
Section:  Social Community Member Relationshipmentioning
confidence: 99%
“…Amorim, Rosa, and Santos (2014) explained that customer-to-customer interaction is a broad concept that refers to a range of interactions that take place between customers during service delivery. For example, customers often talk with each other to exchange information, such as asking for advice or opinions about the suitability of an item for a specific purpose or occasion, which smoothens the service process in the retail setting (K. Harris, Davies, & Baron, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Customers' needs satisfaction can be reinforced through participation behavior, as can the benefits they seek. Similarly, customer participation enhances the service quality (Amorim, Rosa, & Santos, 2014). This enhancement encourages customers' behavior intentions and, as a result, firms' market share, sales, and profits (Dagger, Sweeney, & Johnson, 2007).…”
Section: H5bmentioning
confidence: 99%